A phenomenological investigation of the emotional experiences of elite Brazilian coaches - Vieira, Caroline (2014)
Coaches of elite athletes often need to work under stressful conditions and therefore may experience moments where emotional intensity is running very high. As a result, their physical and mental well-being may be affected. Nevertheless, little attention has been given to the emotional side of the coaches in current scientific literature (Potrac, Jones, Purdy, Nelson, & Marshall, 2013). With this in mind, the purpose of this study was to explore coaches’ stressors and other pleasant and unpleasant emotional experiences related to their coaching performance. Specifically, coaches’ awareness of their emotions and situational triggers were examined.